CFD simulation of stirred tanks: comparison of turbulence models (Part II: axial flow impellers, multiple impellers and multiphase dispersions) - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
In the first part of the review, published literature regarding the CFD modelling of single-phase turbulent flow in stirred tank reactors with radial flow impellers was critically analysed. A brief overview of different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model and large eddy simulation) as well as impeller baffle interaction models has been presented in the previous part. This part is concerned with the review of literature regarding CFD simulation of axial flow impellers. Comprehensive simulations have been carried out using various turbulence models and the model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. The strengths and weaknesses of various turbulence models for axial flow impellers is presented. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-e model as well as Reynolds stress model. Literature efforts on multiple impeller systems and multiphase systems have been discussed in a separate section. Based on these results, suggestions have been made for the future work in this area.
Keywords: axial flow impellers; CFD; impeller models; stirred vessel; turbulence models

CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel

Modeling G-L-L-S reactor: a case of hydrogenation of nitrobenzene - Sharma, Deepankar V.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2017)
Gas-liquid liquid solid (GLLS) reaction systems are often encountered in manufacturing of fine and specialty chemicals. More often than not, such reaction systems involve multiple reactions, and selectivity toward the desired component always poses challenges. An adequate understanding of various parameters affecting GLLS reactor performance is essential to develop strategies for realizing desired selectivity. In this work, a comprehensive reaction engineering model for simulating four phase hydrogenation reactions has been developed. A generalized mixing cell based framework for a reaction system with four interacting phases (gas [G], aqueous [L], organic [L], and solid catalyst [S]) was developed. The model is written in a general way so as to specify one of the liquid phases as a continuous phase, and the other three phases are dispersed into it. In each cell, vapor space is included. The model includes the possibility of evaporation of solvent and internal condensation (in vapor space). The model can also be applied for a dead end (from a perspective of reacting gas) reactor. Model equations were solved using MATLAB. The equations and solution methodology were verified by comparing numerical solutions with available solutions of various limiting cases. A case of four phase hydrogenation of nitrobenzene to para amino phenol and aniline was considered to illustrate the application of the developed model. Key findings from the model were validated by comparing with laboratory scale experimental data. The model was then used to develop insights and guidelines for enhancing selectivity toward desired product. The developed model and presented results will be useful to develop general guidelines for design and optimization of GLLS reactors.

Optimization of Liquid Organic Hydrogen Carrier (LOHC) dehydrogenation system - Rao, Nihal; Lele, Ashish K.; Patwardhan, Ashwin W. (International Journal of Hydrogen Energy, 2022)
In this paper, the perhydrodibenzyltoluene dehydrogenation flowsheet has been simulated. Modelling of the dehydrogenation reactor has been performed using the 1-D model. External and internal mass transfer resistances are also considered. Non-isothermal pellet condition has been considered for simulating the dehydrogenation reactor. The flowsheet simulation has been carried out in DW-Sim v 6.5.2 integrated with the reactor model coded in Python. NET. The dehydrogenation reactor is operated at a feed temperature between 523 K -613 K, a wall temperature of 623 K and 653 K, and a reactor pressure maintained at 1.2 atm. The amount of catalyst required for the perhydrodibenzyltoluene (PDBT) dehy-drogenation reactor is evaluated such that the conversion reaches 99%. The process flowsheet has been simulated to produce 10 Nm(3)/hr of industrial-grade hydrogen. The effects of feed temperature, wall temperature, and hydrogen burner efficiency on various system requirements, including catalyst weight, energy supplied to the dehydrogenation reactor, areas of the heat exchanger, and hydrogen production from the reactor, have been discussed. Preliminary cost optimization based on the heat exchangers and catalyst at various feed temperatures, reactor wall temperature, and hydrogen burner efficiency has been carried out. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Dehydrogenation; DWSim; LOHC; Perhydrodibenzyltoluene; Python; simulation